Application of Behavioral Architecture in The Land Arrangement of class IIA women Penitentiary Institution in Sidoarjo. - Farania, Friza Izatul; Poedjioetami, Esty; Ramadhani, Suci (Faculty of Civil Engeneering and Planning - ITATS, 2023)
Abstract. Penitentiary Institution is a place to carry out coaching for the residents inside. According to the Law, the coaching process of women penitentiary residents must be inside the institution. The existence of a special prison for women can be a solution for empowering and fostering inmates, especially women so that they can be organized and systematic. Using the theme of behavioral architecture, which discusses human relations with the surrounding environment, of course, the psychology of penitentiary residents as human beings must be considered.Class IIA Women Penitentiary in Sidoarjo apply the theme of Behavioral Architecture and use the Security concept to provide a design appearance that gives a strong impression and is able to influence coaching activities both directly and indirectly. The design of the land arrangement uses the concept security applied in layered fences, layered doors, and guard posts.Keywords: Penitentiary, Women, Sidoarjo City, Behavioral Architecture, Humane.